Analysis of cytogenetics for the aneuploids in pentaploid progenies from intergeneric cross between Brassica napus and Orychophragmus violaceus - WU Jian-guo; SHI Chun-hai; LI Zai-yun; FU Ting-dong (浙江大学学报. 农业与生命科学版, 2002)
Cytological observation on progenies of intergeneric pentaploids between Brassica napus and Orychophragmus violaceus was conducted and the results indicated that frequency of cells with 47, 44 and 41 chromosomes in somatic cells or pollen mother cells (PMCs) was higher than that with other chromosome number in aneuploids among the aneuploid progenies. Except for the plants with 38 chromosomes, they were mixoploid with extra chromosomes derived most likely from O. violaceus. Chromosome elimination, due to exclusion from telophase nuclei and sebsequent digestion of the extra chromosomes, occurred in all PMCs (2n>38). Some modes of segregation that were apt to cause symmetrical distribution of chromosome in PMCs at the metaphase Ⅰ (MI) stage. Moreover, several special segregation modes were discovered in PMCs which led to aggregation of 18 or 17 chromosomes at this stage. In each of three parts (anaphase Ⅰ (AI) stage of PMCs, female gametes and male gametes), chromosome number was lowered in plants with 44 or 41 chromosomes according to gamete constitutes and frequency. Among these three parts, the ratio of male gametes with decreased chromosome number was larger than both of others. Gametes with lower chromosome numbers (n=22-19) were more easily transferred to offsprings. Somatic chromosome diminution was observed in root tips of seedling according to their somatic constituent.